f(x)=3x^2-3x, f (0)=, f (-1)=, f (2)=

f(x)=3x^2-3x, f (0)=, f (-1)=, f (2)=

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

plug, then chug.

what you mean plug than chug

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.